Storage behavior and improving seed and seedling quality of the endangered tree species, Agathis borneensis Warb., using biopriming treatments - Naning Yuniarti; Dede J. Sudrajat; Yulianti; Muhammad Zanzibar; Nurhasybi; Kurniawati Purwaka Putri; Nurin Widyani; Yosephin Martha Maria Anita Nugraheni; Evayusvita Rustam; Ratna Uli Damayanti; Surono; Nina Mindawati; et al. (Forest Science and Technology)
Agathis borneensis Warb. propagation, an endangered tree species with high conservation and economic value, is often hampered by a rapid decline in seed quality. This study aims to investigate the effects of storage periods and biopriming treatments using effective microorganism-4 (EM-4) and dark septate endophyte (DSE) (Cladophialophora nyingchiensis) on the viability and vigor of A. borneensis seeds. The seed storability test was conducted conventionally by storing seeds in an air-conditioned room for 0, 1, 2, and 3 months, and then testing their moisture content and germination capacity. Biopriming testing used a factorial, completely randomized design with three treatments (storage period, EM4 and DSE treatments, and soaking time). Based on storability, A. borneensis have seed characteristics that are closer to recalcitrant, as indicated by a decrease in germination capacity, moisture content, and storage time Our study showed that for one month of seed storage, seed soaking in 0.3% EM4 for six hours gave the best germination capacity, germination speed, and germination simultaneity, followed by DSE for six hours (the best for germination value, radicle length, seedling height, seedling biomass, and seedling quality index). EM4 and DSE treatments did not provide significantly positive results for seeds with very low germination capacity (5% and 3.3%, respectively, during two and three-month storage periods). Biopriming with EM4 and DSE effectively increased the germination capacity and growth of A. borneensis seedlings on the seeds with a germination capacity that is not too low (>36%). Technology can be considered useful for germination and seedling production. Successful conservation of the species involves many other steps after germination and seedling production.